Trechus from Ethiopia with Aedeagus Right Side Superior in Repose, an Unusual Character State in Trechine Beetles (Coleoptera: Carabidae) - Joachim Schmidt; Yeshitla Merene; Yitbarek Woldehawariat; Arnaud Faille (Insects)
The Miocene volcano Mt. Choke in northern Ethiopia is known for its very species-rich Trechus fauna. In addition, the enormous morphological diversity that is expressed within a single subgenus, Abyssinotus, which is endemic to northern Ethiopia, is unique within the global Trechus fauna. In this paper, we describe eight additional new species and three subspecies of the Trechus subgenus Abyssinotus, all of which are endemic to Mt. Choke. These species belong to two different lineages within Abyssinotus, each differing from other lineages of the subgenus by certain morphological character states described in this paper and alternatively named the T. lobeliae and the T. basilewskianus subgroups. Several species of these subgroups are characterised by an apomorphical inverse male genital, with the right side up in repose. The T. lobeliae subgroup comprises two species and is monomorphic with respect to this character. The T. basilewskianus subgroup comprises eight species, including six species with monomorphically inverse male genitalia and two species with male genitalia monomorphically in the ‘normal’ position. These are the first examples within Trechinae in which inverse male genitalia are a species- or even group-specific characteristic. A brief summary of the distribution of this trait within the Carabidae is provided. We also present a new identification key for the Trechus species known so far from Mt. Choke.